Angular analysis and differential branching fraction of the decay B0s → ϕμ+μ- - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; et al. (Journal of high energy physics, 2015)
An angular analysis and a measurement of the differential branching fraction of the decay Bs0 → ϕμ+μ− are presented, using data corresponding to an integrated luminosity of 3.0 fb−1 of pp collisions recorded by the LHCb experiment at √s=7 and 8 TeV. Measurements are reported as a function of q2, the square of the dimuon invariant mass and results of the angular analysis are found to be consistent with the Standard Model. In the range 1 < q2 < 6 GeV2/c4, where precise theoretical calculations are available, the differential branching fraction is found to be more than 3σ below the Standard Model predictions.
Im Titel sind "+", "-" und "0" jeweils hochgestellt und "s" tiefgestellt, dabei steht "0" über "s"
The LHCb Collaboration: R. Aaij, B. Adeva; M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, M. Britsch, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, M. Fontana, E. Gersabeck, L. Grillo, O. Grünberg, X. Han, S. Hansmann-Menzemer, A. Jaeger, K. Matthieu, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Schmelling, M. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, A. Zhelezov [und 686 weitere]
Gesehen am 01.04.2021